1998
DOI: 10.1002/(sici)1521-3757(19980504)110:9<1339::aid-ange1339>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Redoxaktive Nanoröhren aus Vanadiumoxid

Abstract: Anders als die viel kleineren Kohlenstoffnanoröhren erhält man VOx‐Nanoröhren (Bild rechts) als Hauptprodukt einer direkten chemischen Synthese bei recht niedrigen Temperaturen. Die Röhrenwände sind mehrschichtig, und zwischen den Schichten befinden sich Templatmoleküle, die durch Kationenaustausch unter Erhaltung der Röhren entfernt werden können.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 0 publications
1
45
0
4
Order By: Relevance
“…Pioneering work on the synthesis and electrochemical properties of vanadium oxide nanorolls was carried out by Spahr et al [53] In their synthesis, a combination of sol-gel reaction and hydrothermal treatment of vanadium oxide precursor is conducted in the presence of an amine that acts as structure-directing template. [53,[54][55][56][57] The resultant nanoroll is either constructed in closed concentric cylinders (nanotubes) or formed by scrolling one or more layers (nanoscrolls). If amine is replaced by ammonia during the hydrolysis step, a new type of vanadium oxide nanoroll (nanotube) with alternating interlayer distances is obtained.…”
Section: Reviewmentioning
confidence: 99%
“…Pioneering work on the synthesis and electrochemical properties of vanadium oxide nanorolls was carried out by Spahr et al [53] In their synthesis, a combination of sol-gel reaction and hydrothermal treatment of vanadium oxide precursor is conducted in the presence of an amine that acts as structure-directing template. [53,[54][55][56][57] The resultant nanoroll is either constructed in closed concentric cylinders (nanotubes) or formed by scrolling one or more layers (nanoscrolls). If amine is replaced by ammonia during the hydrolysis step, a new type of vanadium oxide nanoroll (nanotube) with alternating interlayer distances is obtained.…”
Section: Reviewmentioning
confidence: 99%
“…The VO x NT's present several potential technological applications, such as sensing elements [13], catalysis [14] and Li-ion batteries cathodes [15]. In the last case, it was found that the amount of V 4+ in the structure is critical as it affects and reduce notabily the performance of the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotubes of oxides of several transition metals, as well as of other metals, have been synthesized by employing different methodologies [24,[216][217][218][219][220]. Silica nanotubes were first produced as a spin-off product during the synthesis of spherical silica particles by the hydrolysis of tetraethylorthosilicate (TEOS) in a mixture of water, ammonia, ethanol and D,L-tartaric acid [216].…”
Section: Electronic and Electrochemical Devicesmentioning
confidence: 99%
“…Redox catalytic activity is also retained in the nanotubular structure. There have been efforts to prepare V 2 O 5 nanotubes by chemical methods as well [219].…”
Section: Electronic and Electrochemical Devicesmentioning
confidence: 99%
See 1 more Smart Citation